The Jesus of History - Glover, T. R. (Terrot Reaveley) (New York Association Press, 1919)
This book has grown out of lectures upon the historical Jesus given in a good many cities of India during the winter of 1915-16. Here and there are incorporated passages (rehandled) from articles that have appeared in the Conservative quarterly, the Nat
This book has grown out of lectures upon the historical Jesus given in a good many cities of India during the winter of 1915-16. Here and there are incorporated passages (rehandled) from articles that have appeared in Conservative quarterly, the Nation, t
Keywords: Jesus Christ -- Historicity. Jesus Christ. Historicity of Jesus Christ